Simple and Low-Cost On-Package Sticker Sensor based on Litmus Paper for Real-Time Monitoring of Beef Freshness - Kuswandi, Bambang; Damayanti, Fitria; Jayus, Jayus; Abdullah, Aminah; Heng, Lee Yook (Journal of Mathematical and Fundamental Sciences, 2015)
A simple sticker sensor has been constructed using litmus paper and tests have been conducted to detect the freshness of beef samples. The results show that the sticker sensor can be used to determine the degree of beef freshness, since the color change of the litmus paper and the quality degradation of the beef during storage time had a similar trend, where the decay of the beef could be detected clearly (when the red litmus paper changed to blue). The sticker sensor reacted accurately to the beef's freshness in terms of pH change due to beef deterioration from pH 5.61 to 6.24 and from pH 5.67 to 6.02 as shown by its color change in real time at room and chiller temperature respectively. Thus, the sticker sensor can be used as an effective tool for monitoring the microbial quality of packaged fresh meat that correlates with the increased pH of the beef, where the total viable count (TVC) of 5 x 106 cfu/g or 6.698 log cfu/g correlates with a pH of 6.24. These levels were reached at 10 hrs and 7 days at room and chiller temperature respectively. This study provides a foundation for developing a simple sensor for beef freshness.